The diffusion of novel signs beyond the dyad - Galantucci, B.; Theisen, C.; Gutierrez, E.; Kroos, Christian; Rhodes, T. (Elsevier, 2012)
We present a study aimed at investigating how novel signs emerge and spread through a community of interacting individuals. Ten triads of participants played a game in which players created novel signs in order to communicate with each other while constantly rotating between the role of interlocutor and that of observer. The main result of the study was that, for a majority of the triads, communicative success was not shared by the three dyads of players in a triad. This imbalance appears to be due to individual differences in game performance as well as to uncooperative behaviors. We suggest that both of these are magnified by the social dynamics induced by the role rotations in the game.